1993
DOI: 10.1055/s-0038-1649569
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolytic and Haemorrhagic Effects of Bolus Doses of Tissue-Type Plasminogen Activator and a Hybrid Plasminogen Activator with Prolonged Plasma Half-Life (K2tu-PA: CGP 42935)

Abstract: SummaryK2tu-PA is a hybrid plasminogen activator linking the kringle 2 domain of tissue-type plasminogen activator (t-PA) to the catalytic protease domain of single-chain urokinase-type plasminogen activator (scu-PA). K2tu-PA, as t-PA has high affinity for fibrin and is activated by fibrin but has a longer plasma half-life (over 30 min). The aim of this study was to compare the effects of bolus doses of recombinant t-PA (rt-PA) and K2tu-PA, on: 1) lysis of preformed thrombi (fibrinolysis), 2) accretion of new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The effect of the presence of kringle 2 on the fibrinolytic properties of K 2 tu-PA has been extensively described by Colucci et al (5). Animal studies in dogs (coronary thrombosis model) and rabbits (jugular vein thrombosis model and ear bleeding model) indicated that K 2 tu-PA has potent thrombolytic properties with a prolonged plasma half-live, which may allow administration via an intravenous bolus injection (6)(7)(8). After a dose finding study in patients with acute myocardial infarction (9), a phase II trial was performed in 241 patients with acute myocardial infarction, which showed a high TIMI grade 3 flow (58%) and TIMI grade 2 and 3 flow (76%) at 60 min (10).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the presence of kringle 2 on the fibrinolytic properties of K 2 tu-PA has been extensively described by Colucci et al (5). Animal studies in dogs (coronary thrombosis model) and rabbits (jugular vein thrombosis model and ear bleeding model) indicated that K 2 tu-PA has potent thrombolytic properties with a prolonged plasma half-live, which may allow administration via an intravenous bolus injection (6)(7)(8). After a dose finding study in patients with acute myocardial infarction (9), a phase II trial was performed in 241 patients with acute myocardial infarction, which showed a high TIMI grade 3 flow (58%) and TIMI grade 2 and 3 flow (76%) at 60 min (10).…”
Section: Discussionmentioning
confidence: 99%
“…Amediplase (K2tu‐PA, CGP 42935, MEN 9036) consists of the kringle 2 domain of t‐PA (1–3 + 176–275) and the protease domain of single‐chain urokinase (159–411) [88] . The 356‐amino‐acid enzyme has a molecular weight of about 39.9 kDa and is produced in CHO cells [89] .…”
Section: Third‐generation Plasminogen Activatorsmentioning
confidence: 99%
“…The 356‐amino‐acid enzyme has a molecular weight of about 39.9 kDa and is produced in CHO cells [89] . The half‐life after a bolus injection in rabbits was over 30 min [88] . A study that compared the in‐vitro clot penetration in relation to the fibrin binding of amediplase with alteplase showed 10 times less lysis activity in an internal clot lysis model (injection in the clot) but it was similar in an external model showing that amediplase binding to fibrin was significantly lower, but it had a better clot penetration [90] .…”
Section: Third‐generation Plasminogen Activatorsmentioning
confidence: 99%
“…activator Alter activation in vitro with plasmin, no significant difference was seen in the specific enzymatic activity between purified SSF3-derived K2tu-PA and material derived from transfected standard CHO(dhfr-) cells [8][9][10]. However, 20-60% of the K2tu-PA from the conditioned medium of transfected CHO(dhfr ) cells (if cultured without addition of protease inhibitors) was found to be in the two-chain form and was already enzymatically active prior to deliberate activation with plasmin.…”
Section: Ssf3 Cells Produce Single-chain Recombinant Plasminogenmentioning
confidence: 99%
“…This protein is currently investigated in a clinical trial as treatment for acute myocardial infarction. It is composed of the Kringle-2 domain of human tissue-type plasminogen activator (t-PA) attached to the serine protease domain of the human urokinase-type plasminogen activator (u-PA) [7][8][9][10][11]. Like in the native plasminogen activators, proteolytic cleavage converts the otherwise inactive proenzyme K2tu-PA into an active plasrninogen activator.…”
Section: Introductionmentioning
confidence: 99%